2016
DOI: 10.1155/2016/1717426
|View full text |Cite
|
Sign up to set email alerts
|

First Autologous Cord Blood Therapy for Pediatric Ischemic Stroke and Cerebral Palsy Caused by Cephalic Molding during Birth: Individual Treatment with Mononuclear Cells

Abstract: Intracranial laceration due to traumatic birth injury is an extremely rare event affecting approximately one newborn per a population of 4.5 million. However, depending on the mode of injury, the resulting brain damage may lead to lifelong sequelae, for example, cerebral palsy for which there is no cure at present. Here we report a rare case of neonatal arterial ischemic stroke and cerebral palsy caused by fetal traumatic molding and parietal depression of the head during delivery caused by functional cephalop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Many of the other perinatal and neonatal brain injuries have even less clinical data to support UCB transplantation. A recent study described a case report of UCB administered 4 years after a perinatal stroke that resulted in significant improvement in the subject's motor function (71). No clinical trials in perinatal stroke have been performed, however, and only one is currently ongoing, but has suspended recruitment.…”
Section: Status Of Clinical Administration Of Ucb For Pediatric Brainmentioning
confidence: 99%
“…Many of the other perinatal and neonatal brain injuries have even less clinical data to support UCB transplantation. A recent study described a case report of UCB administered 4 years after a perinatal stroke that resulted in significant improvement in the subject's motor function (71). No clinical trials in perinatal stroke have been performed, however, and only one is currently ongoing, but has suspended recruitment.…”
Section: Status Of Clinical Administration Of Ucb For Pediatric Brainmentioning
confidence: 99%
“…The first autologous transplant of UCB for pediatric ischemic stroke has recently been reported [146]. The work reports a child with right spastic hemiplegia who received 250 million UCB mononuclear cells at 5 years of age.…”
Section: Ucb In Clinical Trialsmentioning
confidence: 99%
“…In particular, early diagnosis is important in children with no aggravated perinatal history, as it allows an early start of therapy, especially with stem cells. Cord blood (CB) has been successfully used in CP in both auto- [2][3][4] and allogeneic [5,6] administrations. Animal studies have shown that the timing of stem cell administration is crucial for the effectiveness of CP therapy [7] and suggest that results may also be time-dependent in humans.…”
Section: Introductionmentioning
confidence: 99%